Improved approaches to genotyping MAOA-uVNTR polymorphisms with novel allele discovery - Areerat Hnoonual; Potchanapond Graidist; Pornprot Limprasert (Scientific Reports)
Abstract A functional polymorphic 30 bp tandem repeat in the upstream regulatory region of the MAOA gene (MAOA-uVNTR) is extensively studied in relation to behavioral and neurobiological traits. The discrepancies of MAOA-uVNTR frequencies may be due to differences in racial and ethnic enrollment and methodologies for detecting alleles. This study aimed to enhance genotyping accuracy of MAOA-uVNTR polymorphisms by comparing conventional PCR and fluorescent PCR methods. Concordance analysis revealed 97.3% agreement (178/183). Discordant results were confirmed by Sanger sequencing, which validated the fluorescent PCR results but identified inaccuracies in conventional PCR findings. The study identified five common alleles (2.5R, 3.5R, 4.5R, 5.5R) and discovered a novel allele, 3.3R, through fluorescent PCR. Functional analysis using luciferase reporter vectors demonstrated 1.5–2.0 times higher transcriptional activity for the 3.3R and 4.5R alleles compared with 3.5R and 5.5R alleles in LA-N-5 and SK-N-SH cell lines. This emphasizes fluorescent PCR as a superior method for identifying MAOA-uVNTR polymorphisms, including novel alleles, with higher resolution and accuracy than conventional PCR. The approach eliminates the need for confirmatory sequencing of known alleles, providing time and cost efficiency. These findings support the use of fluorescent PCR as the preferred technique for accurate genotyping of MAOA-uVNTR and other tandem repeats.